STATISTICAL ANALYSIS OF DRILL PIPE FAILURES OF STRENGTH GROUPS G-105 - Hrabovskyi, R.S.; Tyrlych, V.V.; Vytiaz, A.O. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2022)
Characteristic types of operational defects which formed on the inner or outer surface of drill pipes of strength group G-105 are described. The results of technical diagnostics were used when drilling wells in the territory of the Dnipro-Donetsk gas-oil-bearing region. In 2018-2019, the Ukrburgaz Drilling Department rejected 89 drill pipes of strength group G-105 when drilling wells at a depth of 4,000 to 6,000 meters. A statistical evaluation of operational defects discovered during drilling deep wells (4-6 km) was carried out. Potentially dangerous areas in the drill pipe upset zone, the length of the drill string, and the duration of drilling operations were determined. It is recommended that, when performing defectoscopy of drill string pipes, increased attention should be paid to the section of the pipe from coupling face or nipple, in the range from 0.55 to 0.63 m. In addition, taking into account the depth of drilling, increased attention should be paid to the diagnosis of pipes their placement, since in the interval from 0.43 to 0.52 along the relative length () of the drill string, there is the greatest probability of an operational defect. It is also necessary to pay attention to the duration of drilling operations, in particular, two stages of drilling are distinguished: Stage I – stable operation (up to 6 thousand hours); and the II stage - accelerated destruction (from 6 thousand hours and more), and it was established that during the defect inspection of the pipe, special attention should be paid to drilling pipes, the duration of operation of which in the I stage is from 2692 to 3736 hours, and in the II stage - from 8744 to 10983 hours, since in these periods there is the greatest probability of an unacceptable defect.